S‐100 protein and SOX10‐positive breast carcinoma mimicking metastatic melanoma. (14th September 2020) - Newman, John; Brahmbhatt, Meera; Stoff, Benjamin K.; Martinez, Anthony P.
Abstract: We present a case detailing a 70‐year‐old female with a history of triple‐negative breast carcinoma (TNBC) of the left breast and contralateral stage pT2a nodular melanoma of the right upper arm who underwent sentinel lymph node biopsy of the right axilla demonstrating a metastatic epithelioid tumor that was strongly positive for S‐100 protein and SOX10. The tumor cells were negative for HMB‐45 and Melan‐A and positive for CK7 and other breast markers (GCDFP15, mammaglobin, and GATA3). While concerning for metastatic melanoma based on clinical history and initial immunohistochemistry, tumor morphology and subsequent immunohistochemistry was supportive of metastatic breast adenocarcinoma. This case demonstrates a rare but perilous diagnostic pitfall of triple‐negative breast carcinomas that strongly and diffusely express S‐100 protein and SOX10 mimicking melanoma.